Experimental Study on Measurement of Drag Coefficient of Sandy Soil Nonlinear Vadose - Yu-ping Xu; Jing-yuan Liu; Xiu-wei Chai; Sha-sha Shi (Advances in Civil Engineering)
The seepage characteristics of sand affect its strength, mechanical deformation characteristics, and find safety and stability. The drag coefficient is a dimensionless physical quantity expressing the interaction between fluid and particles, it is also an important parameter that characterizes the permeability of granular soils. Through the seepage test of standard sand with single particle sizes and different grades, analyze the seepage laws of standard sand with different particle sizes in the Darcy and non-Darcy seepage. The relationship between parameters a and b in the seepage equation and porosity (n), average particle size (d50), nonuniformity coefficient (CU), and curvature coefficient (CC), and their influence degree were studied. An empirical formula for determining the permeability coefficient of standard sand is established. By adding a correction factor and verifying its rationality, the empirical formula of standard sand permeability parameters is finally obtained.